Importance of Incidental Findings in Preoperative Computed Tomography Angiography for Abdominally Based Free Flap Breast Reconstruction: A Multi-Institutional Study. Issue 3 (24th June 2022) - Colakoglu, Salih; Yang, Jerry; French, Mackenzie M.; Winocour, Julian; Um, Grace T.; Blumenauer, Brian; Siddikoglu, Duygu; Mureau, Marc A. M.; Chong, Tae; Higdon, Kent; Perdikis, Galen; Inchauste, Suzanne M.; et al.
Abstract : Background: In addition to its intended purpose of perforator mapping, computed tomography angiography can also identify incidental findings that may require further evaluation. In this multi-institutional study, the authors evaluated the frequency of incidental findings and their significance and effects on treatment course and aimed to identify risk factors for detecting such findings. Methods: A retrospective review of patients who underwent perforator mapping with computed tomography angiography was performed over a 5-year period from three academic institutions. Relevant sociodemographic and clinicopathologic information, computed tomography angiography reports, follow-up visits, and treatment outcomes were reviewed. Univariate and multivariate analyses were performed to assess the relationship between risk factors and incidental findings. Results: From January of 2015 to July of 2020, a total of 656 patients were identified who met inclusion criteria. Overall, 342 incidental findings were found, 76 of which required additional imaging or consultation. Ultimately, 10 patients (1.5 percent) had findings that altered reconstructive management, including five patients (0.8 percent) having severe disease that resulted in the cancellation of their reconstruction. Advanced age and immediate reconstruction timing were independent risk factors for incidental findings. Conclusions: Incidental findings are commonly identified on preoperative computed tomography angiography for deep inferior epigastric perforator flap breast reconstruction. Suspicious findings should be investigated thoroughly because they can alter the reconstructive course. Understanding of high-risk groups for incidental findings can further advance patient education during initial consultation. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.